Clinical investigation of matrix metalloproteinases, tissue inhibitors of matrix metalloproteinases, and matrix metalloproteinase/tissue inhibitors of matrix metalloproteinase complexes and their networks in apical periodontitis - Martinho, Frederico C. [UNESP]; Teixeira, Flávia F.C. [UNESP]; Cardoso, Flávia G.R. [UNESP]; Ferreira, Nádia S.; Nascimento, Gustavo G.; Carvalho, Cláudio A.T. [UNESP]; Valera, Márcia C. [UNESP] (Elsevier, 2016)
Introduction This clinical study investigated the levels of metalloproteinases (MMPs) and their tissue inhibitors (TIMPs) and respective forms (MMP/TIMP complexes) in apical periodontitis to determine their networks in the development of clinical/radiographic features, thus quantifying the levels of endotoxins (lipopolysaccharides) present in primarily infected root canals with apical periodontitis. Methods Twenty primarily infected root canals with apical periodontitis were selected. The presence of pain on palpation, tenderness to percussion, and the size of the radiographic lesion were recorded. The levels of MMPs (MMP-1, -2, and -9), TIMPs (TIMP-1 and -2), and their MMP/TIMP complexes (MMP-1/TIMP-1, MMP-1/TIMP-2, MMP-2/TIMP-1, MMP-2/TIMP-2, MMP9/TIMP-1, and MMP-9/TIMP-2) present in the periapical interstitial fluid were measured using the enzyme-linked immunosorbent assay. The kinetic chromogenic LAL test was used to quantify endotoxins. Results A higher mean level of MMP-9 (968.35 ± 342.00 pg/mL) was followed by MMP-2 (894.00 ± 591.62 pg/mL) and MMP-1 (789.43 ± 342.83 pg/mL). The linear regression analysis revealed a positive association of MMP-1 with both MMP-2 and MMP-9 (all P <.001). TIMP-1 (481.79 ± 86.09 pg/mL) (24/24) was found in higher levels than TIMP-2 (206.45 ± 86.09 pg/mL) (P <.05), including a positive correlation of MMP-1 with both TIMP-1 and TIMP-2 (all P <.05). Higher mean levels of MMP1, -2, and -9 were found in teeth with larger-size radiolucent lesions (>7 mm) compared with smaller ones (≤7 mm) (all P <.01). Higher levels of MMP-1 decreased the chance of TTP, whereas MMP-9 (odds ratio = 0.97) increased the chance of pain on percussion (odds ratio = 1.01). Higher levels of endotoxins present in root canals were positively correlated with larger amounts of MMP -9 (P <.05). Conclusions MMPs, TIMPs, and their complexes (MMP/TIMP) are involved in apical periodontitis by interacting with complex networks in the development of clinical features and the severity of bone destruction.
Keywords: Endodontics; endotoxin; infection; root canal